Relationships and phylogenetic revision of Filistatinella spiders (Araneae:Filistatidae) - Fiorini de Magalhaes, Ivan Luiz (2017)
Filistatids represent an antique lineage of araneomorph spiders which are most diverse in arid and semiarid regions of the globe. Phylogenetic relationships among its genera are still largely unexplored, and previous studies disagree on the position of the North American Filistatinella Gertsch & Ivie, 1936, which could either be the sister group of all other, Prithinae, or deeply nested in the subfamily. We present a new phylogenetic hypothesis based on morphological data, which supports the position of Filistatinella at the base of Prithinae. We also argue that the central Asian Pholcoides Roewer, 1960, hitherto considered incertae sedis in the subfamily, represents the putative sister group of Filistatinella. The latter genus is revised, and we describe its fine morphology in detail using optical and scanning electron microscopy. We redescribe the three previously known species, F. crassipalpis (Gertsch, 1935), F. domestica Desales-Lara, 2012 and F. palaciosi Jiménez & Palacios-Cardiel, 2012. Seven new species are named: F. kahloae, sp. nov. and F. chilindrina, sp. nov. from Mexico; F. pistrix, sp. nov., F. tohono, sp. nov., F. howdyall, sp. nov. and F. hermosa, sp. nov. from south-western USA; andF. spatulata, sp. nov. from the border between the two countries. The phylogenetic relationships among these 10 species are assessed, revealing the monophyly of the genus.